The Impact of Leadership Syles on Project Success: The Mediating Role of Team Collaboration - Asmahan Majed Altaher (21393797) (2024)
This study investigates the impact of different leadership styles on project success, specifically examining the mediating role of team collaboration. This study utilized a diverse sample of 202 respondents representing five distinct national contexts: Jordan, Saudi Arabia, China, Australia, and the United Arab Emirates. PLS-SEM were employed to analyze the relationships between transformational leadership, transactional leadership, laissez-faire leadership, team collaboration, and project success. Our findings reveal that both transformational and transactional leadership styles are positively associated with project success. Conversely, laissez-faire leadership demonstrated a negative relationship with team collaboration but did not directly predict project success. Importantly, team collaboration was found to mediate the relationship between both transformational leadership and project success, as well as between transactional leadership and project success. However, the hypothesized mediating role of team collaboration between laissez-faire leadership and project success was not supported. These findings underscore the critical role of leadership style and team collaboration in achieving project success, offering valuable insights for organizations and project managers seeking to optimize leadership practices and foster collaborative work environments. Other Information Published in: Journal of Project Management License: https://creativecommons.org/licenses/by/4.0/   See article on publisher's website: https://dx.doi.org/10.5267/j.jpm.2024.7.001